Motywy wyboru zawodu nauczyciela przez studentów uczelni artystycznych - Joanna M. Łukasik (Edukacja Ustawiczna Dorosłych)
Reasons for choosing the profession of a teacher determine motivation for future work, commitment to the workplace, and good relationship with students. The author of the article focuses on the reasons for choosing teaching as a career path by students of art universities. The aim of the study was to determine the factors behind the choice made by aspiring artists. Although students of art schools point out various reasons for choosing a teaching profession, they are always oriented towards lifelong development. It results from the unique type of education at music schools and close relationship between teachers and students there